Two cases of integrated inventory system - Sarker, M. Ruhul Amin; Karim, A.N. Mustafizul; Azad, G. M. Salam (The Institution of Engineers (IEB), Bangladesh, 1993)
Theoretical inventory control normallv deals with single stage single item case under certain assumptions. However, it gives a picture of inventory problem and starting point of analyzing such problems under realistic environment. Now-a-days there are many variations in analyzing inventory and integrating the interacting parties of inventory system. In this paper. we present mathematical models for integrating the producer and wholesalers' inventory to minimize the overall cost of the system. Similar models can also he presented for raw-material procurement and finished goods production. The benefits of integration will be discussed and numerical exampies will he provided.